Pendampingan Program Pemberian Makanan Tambahan (PMT) Lokal Sebagai Perubahan Status Gizi Balita Desa Jangur Kabupaten Probolinggo - Adhiva Calista Ajiputri; Winda Elmira Amanda; Lala Sevina Putri; Lylu Tirta Damayanti; Katerina Bataha (Cv. Utility Project Solution, 2023)
Providing Local Supplementary Food (PMT) is one of the strategies for handling toddler nutrition problems. Through the assistance of the Local PMT program in Jangur Village, it aims to reduce the problem of malnutrition and the risk of stunting in toddlers. Community service activities carried out by KKNT 55 students at the East Java